System weakness of the criminal procedure legislation in modern Russia - Grinenko, Alexander; Makeeva, Inna (Opción, 2019)
The research objective is to identify problems in the legal coverage of criminal justice in the Russian Federation. The author uses the term "criminal procedure". The necessity of complex changes in the existing criminal procedure legislation with a view to creating a single mechanism for criminal prosecution and protection is described. Among the main conclusions, we want to single out following point: A clear legal status of people involved in criminal proceedings, provided by the law and the mechanism for its implementation. It propels criminal procedure relations to new heights that positively affect the reputation of the social state